2011
DOI: 10.1002/ange.201006031
|View full text |Cite
|
Sign up to set email alerts
|

Architecture‐Dependent Distribution of Mesopores in Steamed Zeolite Crystals as Visualized by FIB‐SEM Tomography

Abstract: Porentief erforscht: Die durch Dampfbehandlung eingeführten Mesoporen in einzelnen ZSM‐5‐Kristallen wurden mit einer Kombination aus fokussierten Ionenstrahlen (FIB) und Rasterelektronenmikroskopie (SEM) tomographiert (siehe Bild). Dabei wurden quantitative Einblicke in die Breite, Länge, Morphologie und Verteilung der Mesoporen erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…In this regard, nothing is more tangible than the direct visualization of the pore architecture 75 . Compared with bulk zeolites, where microscopic techniques are primarily used to determine the particle size and morphology, the multidimensional challenge of examining the structural organization in HOZs has fuelled the development of much more advanced imaging approaches 66 72 76 77 . Fronting this movement, de Jong et al elegantly exemplified the 3D TEM tomographic reconstruction and quantitative analysis of the pore network within commercial USY zeolite crystals 66 76 .…”
Section: Pore Architecturementioning
confidence: 99%
“…In this regard, nothing is more tangible than the direct visualization of the pore architecture 75 . Compared with bulk zeolites, where microscopic techniques are primarily used to determine the particle size and morphology, the multidimensional challenge of examining the structural organization in HOZs has fuelled the development of much more advanced imaging approaches 66 72 76 77 . Fronting this movement, de Jong et al elegantly exemplified the 3D TEM tomographic reconstruction and quantitative analysis of the pore network within commercial USY zeolite crystals 66 76 .…”
Section: Pore Architecturementioning
confidence: 99%
“…Deactivation processes taking place in the FCCU were previously studied by visualization of the structural alterations of the catalyst particle and the zeolite crystal itself, employing various high-resolution imaging techniques. Examples include atomic force microscopy (AFM), [4][5][6] scanning electron microscopy (SEM), [7][8][9][10][11][12] and transmission electron microscopy (TEM). [13][14][15][16][17] These methods provide high-resolution detail, but no correlation was possible between the structure and the activity of the investigated catalyst particles.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstructed models use recent advances in microscopy, enabling three-dimensional imaging of the porous catalytic materials at high resolution [10][11][12][13][14]. Methods for high-resolution microscopy include X-ray tomography [15][16][17][18][19][20] or FIB-SEM techniques [21][22][23][24][25][26] to reconstruct the microporous structure of the catalysts. The images are also used to explore the influence of the reaction rates and effective diffusions within the porous media, improve the accuracy of the chemical-kinetic models, and optimize the design of the washcoat structure [27].…”
Section: Prior Researchmentioning
confidence: 99%
“…Although FIB-SEM techniques have been used to characterize a variety of samples [13,14,[28][29][30][31][32][33][34][35][36], the application of this technique on highly porous media is relatively new and challenging. Prill et al [37,38] used a FIB-SEM technique for 3D reconstruction of a highly porous media and reported that, unlike the batteries and dense surfaces with less porosity, the interpretation of the FIB-SEM data are quite difficult due to the "shine-through" artifacts.…”
Section: Prior Researchmentioning
confidence: 99%